Den hurtige mand MANDSIDEALER I DEN TIDLIGE DANSKE SPORTSBEVÆGELSE - Bonde, Hans (Historisk Tidsskrift, 1988)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The main question posed by the present article is the significance for male history of the sports movement that emerged in Denmark in the period from 1880 to 1914. An analysis of the culture of masculine forms of body movement constitutes the methodological basis for interpreting the role of masculinity in the emerging sports culture. The underlying concept is that the racing geometrical figures of male bodies reflect the contours of a culture based on the cultivation of progress and of expansion in time and space.